Metode Takhrij Hadist Nabi Muhammad Saw. - Fitri Randia Ningsih; Juli Julaiha; Zulfahmi Lubis (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
This article aims to explain about "takhrij hadith" which includes meaning, history, purpose, benefits and methods. From the relevant references it is known that "takhrij hadith" is an attempt to find "matan" and "sanad" hadith, completely from the original reference. It is clear that even the quality of hadith is known to collectors directly through research. The advantages of takhrij hadith are: (a) collecting various "sanad" hadiths; (b) collecting various "matan" hadiths. They are an important material for research. To carry out takhrij hadith, several methods can be used. (1) takhrij hadith based on the first pronunciation of the hadith matan, (2) takhrij based on the pronunciation contained in the hadith matan, (3) takhrij based on the a'la narrator of the sanad hadith (4) takhrij hadith based on the main theme of the hadith. (5) Takhrij hadith based on the form of hadith. Apart from carrying it out manually, takhrij hadith can use technology such as using the maktabah syamilah software on a computer.